Analisis Realisasi Anggaran Biaya Dan Pendapatan Pada Toko Bintang Jaya Rental - Saridawati Saridawati; Puji Astuti; Deti Pratiwi; Mareta Nurul Fitri; Delia Alayda; Nanda Jussi (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
This research aims to determine the analysis of cost and revenue budget realization at Bintang Jaya Rental store. This study employs a quantitative descriptive method. Data collection is conducted through surveys and statistical data analysis to provide an overview or description of the researched object. Budget analysis of expenditure and revenue is the focal point in achieving company success. The research utilizes expenditure effectiveness and efficiency ratios and employs profitability ratio analysis, namely net profit margin ratio. The results and findings of the research indicate that the effectiveness analysis of Bintang Jaya Rental store revenue budget from January to April shows 126.89% (Highly Effective), and the revenue projection for April is 124.79% (Highly Effective). Revenue increases occur during holiday seasons and peak travel periods, leading to a significant increase in car rental demand. The efficiency analysis of cost budget in January and April shows similar results above 90%. Costs are primarily attributed to maintenance, fuel, and driver expenses. Profitability analysis indicates a profit-to-expenditure ratio of 53.84% in January. In April, the average profit level is 50%, influenced by external factors.